2022
DOI: 10.1073/pnas.2118770119
|View full text |Cite
|
Sign up to set email alerts
|

The influence of social norms varies with “others” groups: Evidence from COVID-19 vaccination intentions

Abstract: The theory that health behaviors spread through social groups implies that efforts to control COVID-19 through vaccination will succeed if people believe that others in their groups are getting vaccinated. But “others” can refer to many groups, including one’s family, neighbors, fellow city or state dwellers, or copartisans. One challenge to examining these understudied distinctions is that many factors may confound observed relationships between perceived social norms (what people believe others do) and inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 87 publications
2
15
1
Order By: Relevance
“…Interestingly, heuristic cues about social norms (i.e., bandwagon effect) demonstrated a negative impact on tweet engagement, especially for retweeting. This finding is inconsistent with that of the health behavior literature which often found perceived social norms as a positive predictor of individuals’ health behaviors ( Abdallah and Lee, 2021 ; Rabb et al, 2022 ). This may be because, in the social media persuasion context, audiences perceive emphases of social norms as advertising language, behavioral manipulation, and overly pushy, and thereby resist engaging in the tweets ( Weiger et al, 2018 ).…”
Section: Discussioncontrasting
confidence: 93%
“…Interestingly, heuristic cues about social norms (i.e., bandwagon effect) demonstrated a negative impact on tweet engagement, especially for retweeting. This finding is inconsistent with that of the health behavior literature which often found perceived social norms as a positive predictor of individuals’ health behaviors ( Abdallah and Lee, 2021 ; Rabb et al, 2022 ). This may be because, in the social media persuasion context, audiences perceive emphases of social norms as advertising language, behavioral manipulation, and overly pushy, and thereby resist engaging in the tweets ( Weiger et al, 2018 ).…”
Section: Discussioncontrasting
confidence: 93%
“…Four claims from 2020 focused on how social identities would be highly relevant during the pandemic, particularly how they aligned with either community benefits or social norms. These expectations generally appeared to be accurate, with scores of studies concluding that connectedness with communities or aligning with morals were a predictor of behaviors and controlling the spread of illness 52,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] . However, one challenge that is typically present for research on subjective and latent constructs such as identity, prosociality, and connectedness is that most research was conducted through surveys.…”
Section: Sense Of Identity (Claims 1-4-8-15)mentioning
confidence: 99%
“…Highlighting medical expert agreement about childhood vaccine safety has been shown to increase pro-vaccine attitudes by raising the extent to which the public is aware of expert consensus (e.g., [38] . However, whereas past research on peer social groups has observed high levels of intended COVID-19 vaccine uptake despite low perceived uptake [18] , family members and close friends have been shown to exert a stronger influence on vaccine attitudes and behavior [34] .…”
Section: Introductionmentioning
confidence: 80%